De-Westernisasi Konsep Manusia: Menelaah Konsep Syed Naquib Al-Attas tentang Hakikat Manusia: De-Westenizing the Concept of Man: Examining Syed Naquib Al-Attas' Concept of Human Nature - Nur Shadiq Sandimula (UIN Sunan Kalijaga Yogyakarta, 2022)
Syed Muhammad Naquib al-Attas, the renowned scholar of Islamization of Knowledge, has recognized the defect of the western worldview concerning man, which eventually brought havoc to humanity. Al-Attas' concept of the nature of man is encountered as a critique of the Western conception of man that causes epistemological-conceptual problems severely in the Islamic world. This article aims to conceptualize al-Attas' concept of human nature. This qualitative research employs the content analysis method of al-Attas works. It uses a descriptive-philosophical approach. The result shows that al-Attas conceptualized the concept of human nature based on the concept of insan, which is defined as a living being that speaks. The concept becomes the antithesis of the western worldview's concept of man. Man is a new creation associated with the duality of the soul in the human self. The reality of man is his articulate soul (nafs al-nathiqah), the soul that took Covenant (mitsaq) with God. This soul can overcome the animal's desire in his body through the purification of the soul to achieve a state of soul of tranquility (nafs al-muthmainnah). This state of the soul is marked by the tranquility of the soul and settled happiness (sa'adah). Keywords: Syed Naquib Al-Attas, Islamization of science, humanity, western,eastern